Polygonati rhizoma polysaccharides relieve exercise-induced fatigue by regulating gut microbiota - Jing Xian; Quanlong Chen; Chen Zhang; Qi Huang; Lele Zhang; Jiaqi Ma; Yixuan Feng; Yixi Zhu; Ziye Su; Teng Peng; Wei Xie; Jinming Zhang (Journal of Functional Foods, 2023)
Polygonati rhizoma (known as Huangjing in Chinese), an edible medicinal herb with homology of medicine and food, was also commonly used as food additives in Asian countries to provide many health benefits. Currently, the amelioration of fatigue induced by excessive exercise has become a health concern. In the present study, we studied the anti-fatigue effect of P. rhizoma polysaccharides (PRP) and also explored its potential mechanism by gut flora regulation. The molecular weight, monosaccharide composition, morphology, and FT-IR analysis of PRP were performed. Following intragastric administration of PRP, the exhaustive swimming model mice demonstrated increased swimming time, creatine kinase and malondialdehyde level, decreased lactic acid and blood urine nitrogen levels. Furthermore, the abundance of Akkermansia, Lactobacillus, and Faecalibacterium was remarkably enhanced, while the abundance of Streptococcus and Bacteroides was decreased, compared to model group. In summary, our findings offer compelling evidence supporting the beneficial effects of PRP on exercise-induced fatigue.